Conflict Between The Traditional And Modern Cultures In Khaled Hosseini's A Thousand Splendid Suns Novel (2007): Sociological Approach - Puspitasari, Pipin, Drs. M. Thoyibi, M.S, Titis Setyabudi, S.S., M.Hum (2013)
The problems of the study are "what are the characteristics of the traditional and modern cultures represented in the novel?‟, "how is the conflict between the traditional and modern cultures described in the novel?‟, and "why did the author address the conflict between the traditional and modern cultures in the novel?‟ The objectives of the study are: to identify the characteristics of the traditional and modern cultures, to describe the type of conflict between traditional and modern cultures, and to reveal the underlying reason of the production of Khaled Hosseini‟s A Thousand Splendid Suns novel. The research is qualitative. The primary data comes from the Khaled Hosseini‟s A Thousand Splendid Suns novel itself. The supportive data will be from data related to the study. The conclusions of the study: firstly, the representations of the traditional and modern cultures are classified into five categories: ideas, activities (social practices), artifacts, symbols, and keywords. Secondly, the conflicts between the traditional and modern cultures are described by the conflicts which happen within the characters in A Thousand Splendid Suns novel. Thirdly, there is relation between the production of the novel and the social reality which is the openness of American society in allowing the authors from the third world to write about their homelands or to respond to the events which occur in it.